Development of an Islamic-Based Independent Curriculum Based on the National Curriculum - Daryatmo Rahman; R. Madhakomala (Publikasi Indonesia, 2024)
The background of this research is a study of how to develop an Islamic-based curriculum in informal education in order to provide options and solutions to create an Islamic-based curriculum to develop quality education. The purpose of this research is to develop a curriculum and meet the needs of the community in Islamic educational institutions. In this study, researchers used a qualitative approach while the type of research approach is descriptive with a case study method, which is intended to be used by researchers to describe and explain the development of an independent Islamic-based curriculum based on the national curriculum. The result of this study is that from the changes and developments in the existing curriculum, it turns out that it still does not reach the ideal level to be applied in all educational institutions, so this will have an impact that the curriculum that applies in this country cannot be fully applied in every educational institution, so the development of an independent Islamic-based curriculum will have an influence in improving Islamic education and affecting the fulfillment of community needs for Islamic knowledge.